O governo Dilma Rousseff e a América do Sul: A atuação brasileira na UNASUL (2011-2014) - Fuccille, Alexandre [UNESP]; Mariano, Marcelo Passini [UNESP]; Ramanzini, Haroldo; De Almeida, Rafael Augusto Ribeiro (My University, 2017)
This article sets out to discuss the foreign policy of Dilma Rousseff (2011-2014) in relation to the Union of South American Nations (UNASUR). It examines the direction Brazil wanted that organization to go in when the scope of such South American institutions was widened to formally include new sectors-defense, infrastructure and finance-in regional treaties. After investigating Brazil's actions in those sectors, it found that the government of Brazil: a) sought to support means of governance which were not sufficiently institutionalized; b) wished to reconcile a broad national autonomy with increased commitments to regional mechanisms; and c) did not provide help in forming a regional bureaucracy that would have provided the minimal operational conditions required to support the proposed integrationist initiatives.
The government of Dilma Rousseff and South America. Brazil's actions in the UNASUR (2011-2014)
Keywords: Brazilian foreign policy; Cooperation; Dilma Rousseff; Integration (Thesaurus); South America; UNASUR (authors)